2022
DOI: 10.1590/fm.2022.35120.0
|View full text |Cite
|
Sign up to set email alerts
|

Alteração postural, dor lombar e a resistência dos músculos do tronco em jovens universitárias

Abstract: Resumo Introdução: A lombalgia, transtorno músculoesquelético mais prevalente, é comum em indivíduos com alterações posturais, que são de alta incidência em universitários. Instabilidade e fraqueza dos músculos do tronco podem contribuir para a presença da dor lombar. Não encontrou-se, contudo, pesquisas que tenham investigado a relação da dor lombar em conjunto com as alterações posturais e a resistência dos músculos estabilizadores do tronco. Objetivo: Analisar a correlação entre alterações posturais e res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Regarding the association between postural alterations and low back pain, no statistically significant value was found (p> 0.112) to establish a direct relationship that postural alterations aggravate low back pain symptoms, which can occur independently of a postural problem. According to Fischer 35 in his study with 40 university women, in which they were divided into a group with lower back pain and a control group, the result of the research suggested that there is no direct and significant relationship between postural alterations in young university students with and without lower back pain complaints, thus corroborating the present study. However, Cervantes-Soto et al, 36 in their study with 90 Nutrition and Physiotherapy students in the penultimate semester, found that posture was a determining factor for these students to suffer lower back pain besides having a painful perception due to anti-ergonomic measures of the furniture in the university.…”
Section: Contributions Of the Authorssupporting
confidence: 83%
“…Regarding the association between postural alterations and low back pain, no statistically significant value was found (p> 0.112) to establish a direct relationship that postural alterations aggravate low back pain symptoms, which can occur independently of a postural problem. According to Fischer 35 in his study with 40 university women, in which they were divided into a group with lower back pain and a control group, the result of the research suggested that there is no direct and significant relationship between postural alterations in young university students with and without lower back pain complaints, thus corroborating the present study. However, Cervantes-Soto et al, 36 in their study with 90 Nutrition and Physiotherapy students in the penultimate semester, found that posture was a determining factor for these students to suffer lower back pain besides having a painful perception due to anti-ergonomic measures of the furniture in the university.…”
Section: Contributions Of the Authorssupporting
confidence: 83%